Alveolar development after ligation of left pulmonary artery in newborn pig: clinical relevance to unilateral pulmonary artery. Issue 12 (December 1981) - Haworth, S G; McKenzie, S A; Fitzpatrick, M L
Abstract : The left pulmonary artery and ductus arteriosus were ligated in 14 pigs at birth. Animals were killed at intervals between two and 24 weeks of age. In all animals, serial chest radiographs were taken. In eight animals, nitrogen-13 lung function studies showed normal fractional ventilation in both lungs and continued growth of the small left lung. After death, the fixed inflated volume was determined in each lung an alveolar development was analysed using quantitative morphometric techniques. In the right lung, after operation alveolar size increased considerably and at two weeks was similar to the normal at six months. The normal phase of rapid postnatal alveolar multiplication was delayed from the first to the second month of life. In all animals aged 20-24 weeks alveolar size was almost normal for age and an abnormal increase in alveolar number produced an abnormally large right lung. In the left lung, the alveoli multiplied to achieve a normal alveolar number in all animals sacrificed at 20 and 24 weeks, but the alveoli were abnormally small. Total lung volume was normal in all animals aged 20 and 24 weeks. The structural findings explained the radiographic and radionuclide investigations. The experimental findings are discussed in relation to lung growth in patients with an interrupted pulmonary artery.